Ukraineʼs integration into the digital global space - VYSOCHYN Ірина; ZHUK Олена (Ius Modernum, 2025)
Digitalisation continues to play a key role in ensuring economic growth and sustainable development in the modern world. For Ukraine, digitalisation is not only an important element of domestic development, but also an integral part of its integration into the European digital space. Achieving compliance with the criteria for full EU membership requires the adaptation of national standards to European ones, which creates challenges in maintaining national priorities. At the same time, it contributes to the modernisation of the economy and prepares the country for participation in the EUʼs Digital Single Market, including the harmonisation of the regulatory framework and integration into innovation processes. The research is based on the hypothesis that digitalisation is a key factor in Ukraineʼs post-war recovery, ensuring efficient resource management, stimulating economic growth through innovation, modernization of key sectors of the economy, accelerating integration into the EUʼs Digital Single Market, and creating a sustainable national economy. The research uses comprehensive methods of analysis, including systematisation, comparative statistical analysis and graphical presentation of data. The theoretical part is based on modern concepts of digital transformation, the results of previous studies, as well as data provided by the European Commission, Eurostat and other authoritative sources. Digitalisation provides Ukraine with an opportunity to accelerate its economic recovery, strengthen its position in the international arena and integrate into the European digital space, while safeguarding national interests and enhancing the competitiveness of its economy.